P168 Data analysis of a self-completed questionnaire for patients within a men-having-sex-with-men clinic. (8th June 2017) - Bayman, Philip; Gilson, Rebecca
Abstract : Introduction: The questionnaire was created to discover the characteristics of the MSM population attending a clinic dedicated to their sexual health needs. It covered reasons for attendance, risk factors for sexually transmitted infections and blood-borne viruses transmission and usage of post-exposure prophylaxis and pre-exposure prophylaxis. The data would be used for adaptation of the clinic. Methods: The questionnaire was given to clinic attendees for a 75 day period in 2016 and kept anonymous by a unique client number. The collated data was analysed and reproduced in graph and table form for categories split into reason for attendance. Results: Acceptability of the questionnaire was high at 99.2%. The data analysis showed a large asymptomatic client population (57%) attending the clinic for sexual health screening. For contacts of infection, HIV and gonorrhoea were the most prevalent. For STI and BBV infection risk factors, 15% of clients did not use condoms, while 49% of clients did not know a sexual partner's HIV status. Use of PEP was low but showed a majority using it since 2015, while there were 5 users of PrEP. Discussion: The study showed a majority low-risk MSM population using the dedicated clinic. The survey has influenced clinic redesign with the introduction of test-only clinics for the low risk cohort. However the clinic may not be seeing the high-risk patients who would benefit from senior medical input rather than just a sexual health screen. Data showing usage of PEP and PrEP has given a baseline for comparison in future studies.